Termination of construction contracts by employer - Hosseini, Mohammad Mahdi (2012)
In construction projects, disputes occurrence can have serious impacts; as a client, it is expected to avoid any disputes occurrence during the work; however, it is seemingly inevitable. On such conditions, ideally, it is expected that the express terms and conditions under standard forms of contracts would fairly distribute the risks between the contracting parties. But in reality, some of these clauses, which are set out to prevent or solve those disputes in reasonable time did not perform as expected. For instance, in Iran, General Terms of Contract (GTC) is provided in order to organize procurement systems; however, it could not perform reasonably in some cases in order to prevent or solve the probable destructive impacts of construction disputes. For instance, some of the construction projects under GTC of Iran are abandoned and the contracts are terminated in which the employers will take advantages of the uncertainty of some clauses in GTC of Iran especially termination clauses (clause 46 and 47 of GTC of Iran). But despite GTC of Iran, seemingly this problem, which leads to termination of contract in benefits of employers is less observed in standard form of contract in Malaysia since more details relevant to termination of contract by the parties are clarified in Malaysian standard forms of contracts. For instance, in PWD 203A of Malaysia, termination of contract is explained in rights of both employer and contractor, which include default, procedure and effects (clause 51 – 58). On this basis the issue arises as: what are the most frequent reasons that have caused thetermination of contract in benefits of employer in the actual construction industry? Hence, this study aims to prepare more comprehensive and legally correct conditions and procedure for termination clauses in GTC of Iran in its construction contract by analyzing the most frequent disputes associated with the termination of contract by employer in Malaysian and Iranian construction projects. To achieve this aim, comparative analysis between termination clauses in PWD 203A of Malaysia and GTC of Iran is done with reviewing relevant cases which have been under these standard forms and due to dispute occurrence and termination event referred to the court in Iran and Malaya.